We - Wenhai, Huang (China, 2008)
Verzio FF An unflinching look at China's political system, this film follows men with different generational experiences convinced of the need for a fundamental reform of the political system in China. The people who are juxtaposed in the documentary include a young blogger, who subsequently gets baptized and becomes involved in an underground church, as well as the aged Li Rui, a former secretary of Mao Zedong who was imprisoned for many years, and people close to him - former high-ranking state officials who resisted corruption and are fighting for justice. Among others they debate the need to officially register an opposition organization and the expected retaliation the Communist Party might set off.